ВЛИЯНИЕ КОМПЛЕКСНОЙ ОБРАБОТКИ СЕМЯН КОМПОЗИЦИЕЙ ХЕЛАТИРОВАННЫХ МИКРОЭЛЕМЕНТОВ, СТИМУЛЯТОРОВ РОСТА И ПЛЕНКООБРАЗУЮЩИХ ВЕЩЕСТВ НА АДАПТАЦИЮ РАСТЕНИЙ КУКУРУЗЫ К СОЛЕВОМУ СТРЕССУ (Experimental biology, 2017)
Obtained for hybrid corn seeds encapsulated Tulpar - 539. As part of chelated forms of capsules tested a number of trace elements to increase seed germination and seedling growth under salt stress. Best salt protector in the corn seed capsules confirmed sodium humate - a drug of some microelements chelated by humic acids.
Keywords: capsules; microelements; humic acids